Ethyl acetate as a bio‐based solvent to reduce energy intensity and CO2 emissions of in situ bitumen recovery. Issue 2 (12th November 2019) - Zirahi, Ali; Sadeghi Yamchi, Hassan; Haddadnia, Ali; Zirrahi, Mohsen; Hassanzadeh, Hassan; Abedi, Jalal
Abstract: We introduce ethyl acetate (EA), a bio‐based chemical, as a potential solvent for bitumen recovery through comprehensive phase behavior and numerical simulation studies. Phase behavior and thermophysical properties of EA/live bitumen are measured at temperatures and pressures up to 190°C and 4 MPa, respectively. Experimental studies suggested that coinjection of EA with steam can reduce the bitumen viscosity by several orders of magnitude. Our numerical simulations show that coinjection of 2–8 mol% EA with steam can significantly reduce the steam‐oil‐ratio (SOR) by almost 0.9 units while increasing the bitumen production rate. This reduction in SOR can be translated to significant energy saving of ~2.2 GJ, emission reduction of ~120 kg of CO2, and wastewater reduction of ~120 m 3 per ton of the produced bitumen, which are almost 20–25% lower than the steam‐assisted gravity drainage (SAGD) process.